FEMINISM INTERPRETATION: RECEPTION ANALYSIS OF PEKANBARU SOCIETY ABOUT ‘KARTINI’ MOVIE - Desliana Dwita; Desi Sommaliagustina (Universitas Muhammadiyah Jakarta, 2019)
Film is one of medium of mass communication that brings message to be delivered to target audience. Film is not a value-free entity because it is the result of some people's thinking process until it becomes a cultural product. Hanung Bramantyo's Kartini emphasizes the critical attitude of a woman who broke the injustice in the era of colonization in Indonesia. She can be regarded as the early struggle of feminist figure in Indonesia who have brought today’s Indonesian women no longer experience discrimination in education. Nevertheless, the interpretation of feminism has not been fully accepted because most of Indonesia territories adhere to patriarchal system. The specific objective of this research is to find out the reception of Pekanbaru moviegoers towards Kartini in regard of feminism issue. The long-term goal of this research is to provide feedback for filmmakers about Indonesian audience acceptance towards gender equality issues, and serve as a reference for further research on gender messages in the media. The study used a qualitative research method with the reception analysis approach of the Stuart Hall Encoding / Decoding model which observed assimilation process between media discourse and audience culture discourse. Different understanding on emancipation and feminism causes different interpretation. Informants who have a strong background in life, interpret feminism as a struggle to break injustice. Informants who were in the Dominant Hegemonic Position group were individuals with a high school education background and idolized the figure of Kartini. Informants who are in Negotiated Position are individual observers and film practitioners. Oppositional Position Informants are PhD holder individuals and religious persons. Keywords: Feminism, Reception Analysis, Kartini Movie